Analisis Efisiensi Pemasaran Melon Pada Kelompok Tani “Le Padi Sabee” di Desa Meunasah Dayah Kecamatan Peusangan Kabupaten Bireuen - Khumaira, Khumaira; Puspita, Diah Eka; Fitri, Sri; Zafira, Nada (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to analyze the marketing channels of melon fruit and calculate the profit margins and farmer’s share received by farmers in each channel. The research was conducted at the Le Padi Sabee farmer group in Meunasah Dayah Village, Peusangan Sub-district, Bireuen. The sample consisted of 10 farmers. Two marketing channels were identified: (1) direct sales from farmers to end consumers, and (2) from farmers to retailers and then to end consumers. The results indicate that the first channel provides the highest profit for farmers, with a profit margin of IDR 14,400/kg or 96% and a farmer’s share of 100%, due to the absence of intermediaries and minimal marketing costs. In contrast, in the second channel, farmers sell melons to retailers at IDR 10,000/kg, who then sell them to consumers at IDR 20,000/kg. Retailers gain a profit margin of IDR 4,298.57/kg or 28.62%, with a total margin of 66.6% in this channel. Based on these findings, it is recommended that farmers strengthen direct-to-consumer sales and optimize cost efficiency within distribution channels to increase their income.